Experimental investigation of bluff body geometry effects on nitrogen oxides emissions from Cambridge stratified burner - Morteza Nahvi; Kiumars Mazaheri; Mohammad Zabetian Targhi; Fatemeh Eskandari (Scientific Reports)
Abstract In this study, a series of experiments are done to analyze the effect of bluff body geometry on the NOx reduction of a natural gas-air stratified swirl burner. The stratified burner of Cambridge University is chosen to study the mentioned geometrical effect, and the geometry modification of bluff body is used as a simple method for NOx reduction, which can be easily applied to the systems using these burners, including gas turbines. The bluff body geometrical change to an annular bluff body is inspired by the fact that the areas in which the edge of the bluff body is in contact with the unburned flow have lower temperatures, which can drastically affect combustion parameters, especially emissions. This new geometry is called the Annular Bluff body Stratified Burner, ABSB. The comparison of the mentioned burners is made for three equivalence ratios, Ф, stratification cases: premixed, moderately stratified, and highly stratified with a global equivalence ratio of 0.75, in the conditions of atmospheric pressure and the temperature of the inlet mixture of 26 degrees of Celsius. Flame spectroscopy compares the chemiluminescence intensities of OH*, CH*, C2*, H2O*, and CO2*. Digital image processing, flame edge detection, and exhaust gas analysis are also utilized to measure flames’ general dimensions and emissions. According to experiments, for ABSB cases, a general decrease of about 14% in Nitrogen Oxides, especially NO and NO2, and an increase of about 17% in Carbon Monoxide are observed. Besides, the average bluff body temperature dropped by about 20% in ABSB for all three stratification cases.